Evidence of the sterility of allotetraploid Cobitis loaches (Teleostei, Cobitidae) using testes ultrastructure. Issue 1 (January 2017) - Juchno, Dorota; Pecio, Anna; Boroń, Alicja; Leska, Anna; Jablonska, Olga; Cejko, Beata Irena; Kowalski, Radosław Kajetan; Judycka, Sylwia; Przybylski, Mirosław
GRAPHICAL ABSTRACT: In diploid–polyploid Cobitis populations, C. taenia and C. elongatoides males are fertile and they are the only sperm donors in the reproduction processes whereas tetraploid Cobitis males are sterile and their testes show syndromes of degeneration. Abstract: The diploid–polyploid populations of Cobitis distributed in Poland are usually composed of the spined loach Cobitis taenia or, less often, the Danubian loach C. elongatoides and their triploid (females) and tetraploid hybrids (females and males). The aim of this study was to determine whether tetraploid males participate in the reproduction process by analyzing their testis ultrastructure and the process of spermatogenesis in comparison with diploid males of both parental species. Tetraploid loaches were obtained from three different diploid–polyploid populations distributed in Poland. The structure of Cobitis testes are typical for most Teleostei fish with cystic‐type spermatogenesis. The successive stages of developing germ cells are enclosed within cysts formed by the Sertoli cells. This paper morphologically describes the different germ cell stages of spermatogenesis (spermatogonia, spermatocytes, spermatids, and spermatozoa) of C. taenia and C. elongatoides and provides a pioneering ultrastructural analysis of tetraploid Cobitis testes which reveals their unusual structure for the first time. Thus, cysts with normal spermatogonia and spermatocytes (pachyten or leptoten stages) containing synaptonemal complexes were present and no spermatids or spermatozoa were observed. Moreover, in contrast to previously analyzed diploid species, single cells or all of the cells within the cysts displayed chromatin condensation and/or chromatin fragmentation. The obtained results clearly demonstrated that tetraploid males are sterile and diploids are fertile and are the only sperm donors in the reproduction processes of diploid–polyploid Cobitis populations.